Cantiga de Escarnho galego-portuguesa : sociologia ou poética - Osório, Jorge Alves (2014)
The satyrical «cantigas» of the Galician-Portuguese «cancioneiros» have mainly been interpreted as texts which document the social reality of the 13th. and 14th. Centuries. However, by taking into account the most recent studies on medieval poetics it is reasonable to ask if the meaning of this poetry should be sought on the sociological level, or if (as indeed the author of this article hopes to prove), on the contrary, this poetry should be seen to represent a way of realizing the poetics of the Iberian 13th. Century.